Branding Bawaslu dalam Meningkatkan Kepercayaan Publik terhadap Pengawasan Pemilu: Studi Kasus pada Strategi Branding Bawaslu Kabupaten Ngada - Johanis Aldian Sina Redo; Veki Edizon Tuhana; Henny L.L. Lada (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to identify the branding strategies implemented by Bawaslu Ngada Regency in enhancing public trust in election supervision. This study employs a constructivism paradigm with a qualitative approach and case study method, with data collection through in-depth interviews, social media observations, and documentation involving the Head of Bawaslu Ngada, Public Relations Officer, and Bawaslu Ngada staff. Data analysis uses the Miles and Huberman model with data validity tested through source and method triangulation, and applies David Aaker's Brand Equity theory encompassing dimensions of brand awareness, brand associations, perceived quality, and brand loyalty. The research findings reveal that Bawaslu Ngada Regency implements five main strategies in building brand equity: branding through mass media and social media (Facebook and Instagram); face-to-face community activities through the